Wordwall-Assisted Gamification: Improving Mathematics Learning Outcomes Through Strengthening Motivation and Learning Engagement - Ahmadsyah Fauzian Rambe; Muhammad Nuh (Juring (Journal for Research in Mathematics Learning), 2025)
This study aims to examine the impact of implementing a gamification-based learning model supported by the Wordwall platform on the learning outcomes of seventh-grade students at MTsN 1 Medan, particularly in algebraic factorization. Employing a quasi-experimental method with a pretest–posttest control-group Design, the sample was selected via cluster random sampling from 11 existing classes, with class VII-H designated as the experimental group and class VII-I as the control group. The analysis revealed that this model significantly improved students’ learning outcomes, as evidenced by a t-test with a p-value below 0.05, indicating a meaningful difference between the two groups. Qualitative interviews further revealed that Wordwall effectively enhanced students’ motivation, engagement, and active participation, demonstrating that the model’s implementation has a positive, significant impact on their academic achievement